2017
DOI: 10.3758/s13423-017-1273-0
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linguistic transfer in bilinguals reading in two alphabetic orthographies: The grain size accommodation hypothesis

Abstract: Reading acquisition is one of the most complex and demanding learning processes faced by children in their first years of schooling. If reading acquisition is challenging in one language, how is it when reading is acquired simultaneously in two languages? What is the impact of bilingualism on the development of literacy? We review behavioral and neuroimaging evidence from alphabetic writing systems suggesting that early bilingualism modulates reading development. Particularly, we show that cross-linguistic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 116 publications
(133 reference statements)
10
33
1
1
Order By: Relevance
“…This study supports the hypothesis that a cross-linguistic transfer takes place between the languages of bilingual dyslexic readers (Lallier & Carreiras, 2017). As predicted, dyslexic adults who learned to read in Welsh (a consistent orthography) in addition to English (an inconsistent orthography) showed benefits in literacy tasks engaging phonological processing to a high degree.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This study supports the hypothesis that a cross-linguistic transfer takes place between the languages of bilingual dyslexic readers (Lallier & Carreiras, 2017). As predicted, dyslexic adults who learned to read in Welsh (a consistent orthography) in addition to English (an inconsistent orthography) showed benefits in literacy tasks engaging phonological processing to a high degree.…”
Section: Resultssupporting
confidence: 88%
“…It has been repeatedly shown that learning to read in a consistent orthography promotes the development of sublexical decoding strategies and in turn, the development of phonemic awareness, because the mappings between letters and sounds are simple and consistent (e.g., Seymour et al, 2003). Based on evidence that interactions occur between the two languages of bilingual readers (Lallier & Carreiras, 2017), we hypothesized that the over-reliance on sublexical reading strategies prompted by reading in the consistent Welsh orthography would transfer to English and boost the use of sublexical strategies in this inconsistent orthography too. Therefore, we expected reduced deficits in Welsh-English bilingual readers with dyslexia compared to English monolingual readers with dyslexia on pseudoword reading and spelling as well as phonemic awareness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also seems important to study this relation across orthographies. Although we showed that VAS is an important correlate of reading in a relatively transparent orthography, it has been found that VAS contributes more strongly to reading in deep rather than shallow orthographies (e.g., Lallier & Carreiras, 2017).…”
Section: Discussioncontrasting
confidence: 68%
“…According to this hypothesis, French-Basque bilingual children in the older group must have processed more letters in parallel when performing the task than their Spanish-Basque peers, thus capturing the letters that composed the Basque words as a whole. These results confirm that the effects of orthographic depth can be observed in tasks not directly involving reading (Lallier et al, 2016;Lallier & Carreiras, 2017). Furthermore, the results indicate that there is a degree of multi-letter processing in the RAN that can be enhanced under certain conditions (in this case the insertion of lexical units).…”
Section: Discussionsupporting
confidence: 79%